Banking on FinTech in Emerging Markets - Rose Innes, Cleo; Andrieu, Jacqueline (International Finance Corporation, Washington, DC, 2022)
Despite near-universal access to financial services in advanced economies, financial exclusion is stubbornly persistent in many emerging markets, leaving huge swaths of low-income populations unbanked or underbanked. FinTech companies, which apply innovative technologies to deliver such services in new ways, have begun to tap into the enormous unmet demand that this represents. These companies are starting to thrive in emerging markets, though regulatory issues, particularly weak consumer protection measures, remain to be resolved in many countries. If these can be overcome, and more progress toward universal access to digital infrastructure can be made, FinTechs will continue to scale and spread.